Stat op i Gry, min Gud! Tre gammeltestamentlige salmer, gendigtet af Grundtvig - Holt, Else Kragelund (Grundtvig-Studier, 1996)
Grundtvig 's version of Three Old Testament Hymns By Else Kragelund Holt The article seeks to demonstrate the significance of Grundtvig’s interpretative use of the old Testament in Sangværk /. The methodological inspiration for the study is not to be found in the ongoing Grundtvig research, but in Old Testament exegesis, especially in the shape of Tradition History and Wirkungsgeschickte. The questions raised are not primarily why Grundtvig did so and so with his Old Testament Vorlage, but rather what he did with it. The material of the investigation is three hymns from the Easter part of the Sangværk. According to Grundtvig, SV #206, / de gyldne Himmel-Sale (»In the Golden Halls of Heaven«), was written »after the 16th Psalm of David«. On the basis of its form, this psalm should be designated as a psalm of confidence, i.e. a psalm expressing trust in the Lord’s will to take care of those faithful to him, while life will be burdensome to the godless. The Psalmist presents himself as a man obedient to God (v.2), a man who knows that the Lord has given him counsel (v.7), and that He will not let him meet an untimely death (v. 10). One might expect Grundtvig to use Ps 16 as an expression of the Christian’s joy of life, but this is not what he does. Presumably inspired by Christian Vi’s Danish Bible, he reproduces Ps 16 as a heavenly dialogue between the Father and the Son. The Father consults the Son about how mankind can be delivered. Whereas Ps 16 depicts God as the support of man, Grundtvig uses the words of the psalm as a prediction of Christ supporting the Father’s plan of deliverance. In stanza six the speaker changes: Jesus praises the Father for the help that He will show him, when He is to fight Death. Ps 16, 9-10 becomes a prediction of Jesus’ victory over Death, and Ps 16, 11, correspondingly, a prediction of the Ascension. Grundtvig uses Ps 16 »prophetically«, reinterpreting the Old Testament motif of the guidance of the Lord in a different context. Where Ps 16 has an earthly orientation, the perspective of the reproduction becomes cosmic - and, one might add, part of the Easter service in church. SV #207 - O min Gud, min Gud og Fader! (»Oh, My God, My God and Father!«) is said to be »the 22nd Psalm of David, freely translated«. This is the psalm which opens with Jesus’ last words from the Cross: My God, my God, why hast thou forsaken me? The Old Testament psalm is a personal lament. Vv. 2-22a describe the despair of one, abandoned by God and community, vv. 22b-31 are the praise of a man whose cries have been heard. Grundtvig does not overtly take up the theme of the Passion. Rather he reproduces the psalm very closely, as if to make it usable as a hymn for the Danish church. Nevertheless, a personal adaptation is detectable. First, the hymn talks to God as a father - a divine metaphor, which is not used in the Book of Psalms at all. Here the words from the Cross are traceable. Another vestige of the Passion can be found in the beginning of the hymn, where the poet asks »my God and Father« to »stay with me now«. It seems as if the worshipper has not yet been abandoned, but that he knows that he will be, like Jesus in Gethsemane. Finally, Grundtvig identifies the enemy from whom the worshipper asks to be saved, as Death. In SV #209 - Stat op i Gry, min Gud! stat op! (.Arise at Dawn! My God, Arise.) Grundtvig again translates the Old Testament psalm very closely. PS 68 is a rather martial psalm of thanksgiving for a royal victory, and Grundtvig uses it to portray the victorious resurrection of Christ. Literally between the lines, Grundtvig puts christological interpretations, using allusions to Christmas for instance, and to the Word that bears a giant’s strength. In stanza four Grundtvig changes the reference of the Old Testament psalm to the Wanderings in the Wilderness as a metaphor of fertility and creation (vv. 8-9), using, instead, the stream rising in Eden (Gen 2,4) which he interprets as baptism. What can be concluded is that Grundtvig at the same time re-writes and reinterprets the Old Testament poetry more or less in the tradition of how the Old Testament was re-interpreted in the New.